Effect Of Meat Immersion And Addition Of Liquid Smoke Coconut Shell On The Quality Of Chemical And Antioxidant Of Beef Jerky - Adjis, Asril; Sugiarto, Sugiarto (AgriSains, 2019)
Soaking beef jerky can improve chemical quality, flavor and consumer acceptance of the products produced. Liquid smoke functions as a preservative, a specific flavor and aroma. The research aims to analyze the chemical quality and antioxidant activity of beef jerky that has been soaked with the addition of liquid coconut shell smoke. The study used a Completely Randomized Design (CRD) with 5 treatments (D0 = jerky without soaking and adding liquid smoke, D1 = jerky with 2 hours soaking and adding 1% liquid smoke, D2 = jerky with 4 hours soaking and adding 1% liquid smoke, D3 = beef jerky with 6 hour soaking and 1% liquid smoke addition, D4 = jerky with 8 hour soaking and 1% liquid smoke addition) and 3 replications. Levels of protein, fat, water and antioxidant activity of beef jerky were observed in this study. Data were analyzed variance (ANOVA) with Duncan's further test. Immersion treatment and addition of coconut shell liquid smoke on beef jerky showed a chemical quality that was not statistically different in all treatments, but an increase in protein content (34.28% - 39.28%), fat content (3.98% - 5 , 25%), water content (11.02% - 12.33%) and antioxidant activity (355.23% - 201.98%).